Analysis of agrotourism potential as an alternative economic development in Kawinda To’i, Tambora - Gunawan Gunawan; Husnul Jannah; Amrullah (Journal of Biology, Environment, and Edu-Tourism, 2025)
Agrotourism is recognized as an alternative strategy for rural economic development. Kawinda To’i in the Tambora District features fertile volcanic soils, diverse agricultural commodities, and a strategic location near Tambora National Park. This study analyzes internal–external factors and identifies strategic priorities for sustainable agrotourism development using a mixed descriptive approach incorporating IFE–EFE matrices and qualitative insights. Results indicate strong internal strengths—fertile land, commodity diversity, and cultural local support—alongside key weaknesses such as limited infrastructure and low human resource capacity. External opportunities include strong policy support and rising demand for nature-based tourism, although climate risks and competition with other NTB destinations pose threats. Strengthening local institutions, improving infrastructure, and enhancing community capacity represent the most strategic steps for advancing sustainable agrotourism in Kawinda To’i.